Ocular and cardiovascular pharmacology of tetramethylpyrazine isolated from Ligusticum wallichii Franch - Chiou George C Y; Yan Han-ying; Lei Xun-lan; Li Byron H P; Shen Zhu-fang (Acta Pharmacologica Sinica, 2016)
Tetramethylpyrazine (TMP), the active principle in Ligusticum wallichii, D-timolol, and L-timolol were compared for their effects on retinal and choroidal blood flow (RCBF), blood pressure (BP), and heart rate (HR). TMP (10 mg.kg-1) increased RCBF by 44% and did not affect systemic BP or HR. D-Timolol (4 mg.kg-1 iv) had a tendency to increase RCBF but did not affect systemic BP and HR either. L-Timolol (0.4 mg.kg-1 iv), on the other hand, decreased RCBF by 18% and reduced both systemic BP and HR. In isolated preparations, TMP increased coronary artery blood flow with slight vasodilation, but vasoconstriction in renal, femoral and mesenteric arteries. These results indicate that TMP could be used to prevent or alleviate certain ischemic retinal degenerations without producing significant cardiovascular side effects. The in vitro vasoconstriction actions of TMP (0.2 mg.ml-1) were blocked by propranolol and phenoxybenzamine, indicating that adrenergic mechanism might be involved in TMP action.